If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7(t + -3) + 4t = -3(-7 + t) Reorder the terms: -7(-3 + t) + 4t = -3(-7 + t) (-3 * -7 + t * -7) + 4t = -3(-7 + t) (21 + -7t) + 4t = -3(-7 + t) Combine like terms: -7t + 4t = -3t 21 + -3t = -3(-7 + t) 21 + -3t = (-7 * -3 + t * -3) 21 + -3t = (21 + -3t) Add '-21' to each side of the equation. 21 + -21 + -3t = 21 + -21 + -3t Combine like terms: 21 + -21 = 0 0 + -3t = 21 + -21 + -3t -3t = 21 + -21 + -3t Combine like terms: 21 + -21 = 0 -3t = 0 + -3t -3t = -3t Add '3t' to each side of the equation. -3t + 3t = -3t + 3t Combine like terms: -3t + 3t = 0 0 = -3t + 3t Combine like terms: -3t + 3t = 0 0 = 0 Solving 0 = 0 Couldn't find a variable to solve for. This equation is an identity, all real numbers are solutions.
| (-6)-5= | | (7)(-4)= | | 2x+5=7x-20 | | 2q-4+8q=7q-8+3q | | r+11+8r=11 | | (xy-420)=3x-y | | 7X-(3+2x)=X+9 | | 6(xy-420)=0 | | S=p+prt | | 3h-11=-21 | | 6(xy-420)=3x-y | | Y=-4x-7 | | 7-2(4x-5)=-5x+11 | | 3(X+5)=7-5X | | 7(3-2X)=15(1-X) | | 26-2y=8Y-44 | | 4x-3(x+5)=1-4x | | 3c+4c-12=6+c | | 4(X-9)=3(X-8) | | 3X-420=0 | | 3x+4-5x=2-4x | | 13x-9=3x+10 | | yx(420)=3x | | 4x-7(3x+6)=4x-9 | | 5+3=810 | | 20x=8(x+180) | | 48-3x=5x | | 70-3x=4x | | xy=420 | | 4x+1=3x+3 | | 25-2x=3x+20 | | 9+9x=17+5x |